Cooperación FO-AR-INTA: más de 16 años de historia compartida - Cipolla, Ana L. (Revista Española de Desarrollo y Cooperación, 2023)
INTA focuses its action in the field of technological innovation, to strengthen national, regional and territorial developing, contributing to the social, economic and environmental basis of Agricultural, Food and Agribusiness systems in Argentina (INTA Institutional Strategic Plan, 2005-2015). In order to achieve this goals, three main areas have been selected as objectives: competitiveness, environmental health and social equity. In this context, Institutional Relations, one of four strategic components of INTA, play a key role, allowing the linking between the public and private actors with opportunities for innovation, at the international, national, regional and local levels.